(untitled) (Experimental biology, 2025)
This article explores the growth and adaptation of Juglans nigra in the conditions of Southern Kazakhstan. The study aimed to investigate the species’ morphological, physiological, and anatomical characteristics and to assess the impact of soil and climatic factors on its development. Research tasks included the analysis of phenological phases, biometric measurements, tissue structure studies, and soil property evaluation. The study was conducted at the Botanical Garden of the International Kazakh-Turkish University. Results showed that J. nigra exhibits high adaptability to the regional climate. The vegetation period is marked by steady growth, strong root development, and high plant viability.Soil composition and moisture levels significantly influenced seedling growth. Physiological assessments revealed adaptive mechanisms supporting water balance and drought resistance. Anatomical analysis identified protective structures that reduce water loss and enhance tissue strength.These findings support the potential for J. nigra introduction in arid regions and inform agrotechnical strategies to improve resilience and productivity.